Experimental and Simulation investigations of Micro Flexible Deep Drawing Using Floating Ring Technique - Mahmood, Zaid H.; Irthiea, Ihsan K.; Abed, Kadum A. (Al-Khwarizmi Engineering Journal, 2018)
Micro metal forming has an application potential in different industrial fields. Flexible tool-assisted sheet metal forming at micro scale is among the forming techniques that have increasingly attracted wide attention of researchers. This forming process is a suitable technique for producing micro components because of its inexpensive process, high quality products and relatively high production rate. This study presents a novel micro deep drawing technique through using floating ring as an assistant die with flexible pad as a main die. The floating ring designed with specified geometry is located between the process workpiece and the rubber pad. The function of the floating ring in this work is to produce SS304 micro cups with profile radius precision as required as possible. The finite element simulations are accomplished using the commercial code Abaqus/Standard. In order to verify the simulation models, micro deep drawing experiments are carried out using a special set up developed specifically to meet the requirements of the simulations. The results revealed that the proposed technique is feasible to be adopted for producing micro cups with remarkable application capability in miniaturization technology.